Functional Feeding Group (FFG) of Aquatic Macroinvertebrate in Middle Reach of Kerian River Basin of North Malaysia Peninsula - Nurul Huda Abdul,; Che Salmah Md Rawi, (Tropical Life Sciences Research, 2019)
Investigations on the distribution and abundance of aquatic macroinvertebrates functional feeding group (FFG) in Bogak, Kerian and Serdang rivers of Kerian River Basin showed that there were 120 genera from 59 families of 13 orders of macroinvertebrates. Predator mainly Odonata, Hemiptera and Coleoptera was the most common group and found in high densities in Bogak River (modified river) and Kerian River (main river). The second dominant group in both rivers was collector-gatherer (Diptera and Ephemeroptera) followed by scraper (mollusks). A different pattern of FFG distribution was observed in Serdang River (tributary of Kerian River). The most abundant group was collector-gatherer, followed by predator and scraper. In general, predator abundance showed a significant positive correlation with their prey abundance (other feeding groups). Predator abundance especially in Bogak and Kerian rivers, was significantly influenced by parameters such PO4 3-, NO3 -N and Zn. In Serdang River, collector-gatherer abundance was affected by water temperature, velocity, TSS, turbidity, Mn and Cu content in the sediments. However, all water parameters weakly influenced the abundance of FFGs in all locations. High abundance of collector-gatherer in Serdang River was related to enriched water contributed by anthropogenic waste from surrounding residential areas. In general, dominant FFG in each river reflected the influence of different environmental conditions and availability of food sources in the area. Siasatan terhadap taburan dan kelimpahan kumpulan pemakanan makroinvertebrata akuatik di Sungai Bogak, Kerian dan Serdang di lembangan sungai Kerian menunjukkan terdapat 120 genera dari 59 keluarga dari 13 order makroinvertebrata. Pemangsa terutamanya Odonata, Hemiptera dan Coleoptera adalah kumpulan yang paling biasa dan didapati dalam kepadatan tinggi di Sungai Bogak (sungai yang diubah suai) dan Sungai Kerian (sungai utama). Kumpulan dominan kedua di kedua-dua sungai itu adalah pemungut-kumpul (Diptera dan Ephemeroptera) diikuti oleh pengikis (moluska). Pola kumpulan pemakanan yang berlainan diperhatikan di Sungai Serdang (anak Sungai Kerian). Kumpulan yang paling banyak adalah pemungut-kumpul, diikuti oleh pemangsa dan pengikis. Secara umum, kelimpahan pemangsa menunjukkan korelasi positif dengan kelimpahan mangsa mereka (kumpulan pemakanan lain). Kelimpahan pemangsa terutama di Sungai Bogak dan Kerian, sangat dipengaruhi oleh parameter seperti PO43-, NO3-N dan Zn. Kelimpahan pemungut-kumpul di sungai Serdang pula dipengaruhi oleh suhu dan halaju air, TSS, kekeruhan serta kandungan Mn dan Cu di dalam sedimen. Walau bagaimanapun, semua parameter air mempengaruhi secara lemah kelimpahan kumpulan pemakanan di semua lokasi. Banyak pemungut-kumpul di Sungai Serdang dikaitkan dengan air yang diperkaya oleh sisa antropogenik dari kawasan kediaman sekitar. Pada umumnya, kumpulan pemakanan yang dominan di setiap sungai mencerminkan pengaruh keadaan persekitaran yang berbeza dan ketersediaan sumber makanan di kawasan tersebut.